Challenges of Parents Educating Children's Morals in Muslim Families - Rhadiatul Rahmi; Ramadhani Ramadhani; Nurhasnah Nurhasnah; Silva Namira; Nova Erlina Yaumas (International Journal of Multidisciplinary Research of Higher Education, 2021)
The role of parents in the family is needed in children's education. As times progress, parents have challenges in educating children in the family. The aim of this study is to analyze what is the challenge for parents to educate children's morals in Muslim families. This research uses the method qualitative case study approach. Data sources were taken from four informants through in-depth interviews consisting of traditional leaders, clerics, Islamic religious education teachers, and community leaders who were selected using the technique of purposive sampling. All interview results were analyzed using techniques Analysis Interactive Model Milles & Huberman. Analysis results show that there are five challenges for parents in educating children's morals in Muslim families. The five challenges are: i) The high volume of parents' work, ii) the low knowledge of parents about parenting, iii) the strong currents of globalization, iv) the challenges of modern life, v) the low knowledge of parents about the Islami religion. Research result this can be used as information for the community to be able to find solutions to family problems.